A UTILIZAÇÃO DO EVA (ECONOMIC VALUE ADDED) E OUTRAS FERRAMENTAS PARA O CONTROLE GERENCIAL EM UMA UNIDADE INDUSTRIAL - Pontes, Luís Antônio Longo Pinheiro (2004)
The companies are evaluated on the basis, principally, of the economic-financial indicators. There are some methodologies and models, such as: the project assessment analysis the remuneration program and incentive to executives and analysis of valuation of designs. Nowadays, the two most used concepts of performance assessment the companies are EVA and MVA. The main difference between these concepts and the traditional methods is the EVA and MVA take into consideration the cost of the capital invested by the shareholders. What matters for the growth of a company is the increase of the value generated for the shareholder. This way, in the present work, two useful tools are used for this company performance assessment. This thesis is intended to present the concepts, methodologies and applications of these performance pointers as, also, a correlation between EVA and MVA through research based on statistical tests. Besides standing out possibilities for one better control of the expenditure system for the production, through the concepts of ABC and ABM. It is inserted in the context of productivity improvement, the Six Sigma concept. This universe of analyses regards to the Cryogenic Equipment Factory, a facility of Reappearance Industrial Gases Ltd.